Income tax noncompliance in Nigeria and the moderating effect of public governance quality: a suggested framework - Umar, Mohammed Abdullahi; Derashid, Chek; Ibrahim, Idawati (MCSER-Mediterranean Center of Social and Educational Research, 2016)
Income tax noncompliance is a huge problem in Nigeria making the country one of the lowest income tax countries in the world based on percentage of GDP. The study reviews and integrate previous research and causes of noncompliance were identified – Socio economic condition, tax knowledge, perceived audit probability and prevailing social norm .However, as acknowledged by researchers, over fifty years of research on noncompliance is yet to produce a formula that can solve noncompliance problems applicable to all jurisdictions hence the need to develop country-specific models. Given that Nigeria has one of the largest informal sectors in the world, this study adds perceived attractiveness of the informal sector as a factor and reconstructs public governance quality as moderator of other factors. The study argues that the above factors are present in all countries of the world; if they are worse in Nigeria, then a moderator could be the problem and public governance quality is plausible given Nigeria’s poor record.Facts from previous research support this position.It is recommended that Nigerian government urgently improve on public governance to reduce the size of the informal sector and mitigate the effects of the other factors.Further research is needed to statistically analyse the suggested framework.